2020
DOI: 10.1177/1099800420905889
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox in Sepsis: A Theoretical Framework

Abstract: Sepsis is a life-threatening syndrome that occurs in response to a severe infection. In recent years, the understanding of the pathobiology of sepsis has been refined, with research describing an altered host response as the underlying cause. Survivors of sepsis often have long hospital stays and suffer from subsequent frailty and long-term health consequences. Predicting attributes of sepsis survivors remains challenging; however, an obesity paradox exists, wherein obese individuals survive sepsis at higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…ii) patients experience somatic mutations (39) and inflammageing (40); iii) PCs are weakened due to single nucleotide polymorphism (41); iv) cytokine blockage therapies are used; v) genes encoded PCs and other regulators are knocked-out in mice; vi) inflammation is resurged when MHO undergoes a transition to classical metabolically unhealthy obesity (31,32) in response to the long term stimulation of metabolic disease risk factors such as hyperlipidemia, danger associated molecular patterns (DAMPs) and conditional DAMPs as we reported (42); vii) an obesity paradox exists, wherein obese individuals survive sepsis at higher rates than their normal-weight counterparts (43); viii) inflammation paradoxes are observed in the Amazon region showing that the…”
Section: Introductionmentioning
confidence: 82%
“…ii) patients experience somatic mutations (39) and inflammageing (40); iii) PCs are weakened due to single nucleotide polymorphism (41); iv) cytokine blockage therapies are used; v) genes encoded PCs and other regulators are knocked-out in mice; vi) inflammation is resurged when MHO undergoes a transition to classical metabolically unhealthy obesity (31,32) in response to the long term stimulation of metabolic disease risk factors such as hyperlipidemia, danger associated molecular patterns (DAMPs) and conditional DAMPs as we reported (42); vii) an obesity paradox exists, wherein obese individuals survive sepsis at higher rates than their normal-weight counterparts (43); viii) inflammation paradoxes are observed in the Amazon region showing that the…”
Section: Introductionmentioning
confidence: 82%
“…According to the diabetes paradox, obesity is also protective during critical illnesses, with reports of better outcomes in patients with obesity with ARDS [ 34 ] and sepsis [ [35] , [36] , [37] , [38] ]. The chronic low-grade inflammation status observed in patients with obesity could modulate the sepsis host response, resulting in an attenuated cytokine response, thus leading to lower mortality rates compared to individuals with normal weight [ 39 ]. In our sample, the mean BMI was 30.7 ± 7.2 kg/m 2 , which was higher in survivors than in non-survivors (p = 0.012), corroborating the protective effect of moderate obesity in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the obese have a blunted inflammatory response during acute insults due to inflammatory preconditioning. That is, the heightened state of inflammation prior to the onset of sepsis provides a primed system where anti-inflammatory modulators are already upregulated to combat the chronic pro-inflammatory effects of obesity, thus suppressing the typical exaggerated pro-inflammatory response (5, 7, 8). In addition to prompting secretion of anti-inflammatory mediators, the abundance of pro-inflammatory mediators produced by adipose tissue could also confer protection in the obese due to priming of the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported that falling within an overweight or obese BMI classification appears to confer a survival advantage during sepsis (1)(2)(3)(4)(5)(6). This emerging phenomenon is referred to as the ''obesity paradox'' (5,7,8). While the association between higher BMI and increased survival is reflected in numerous clinical studies, including patients with sepsis as well as other critical illnesses, it is important to acknowledge that controversy exists.…”
Section: Introductionmentioning
confidence: 99%